Post-transplantation cyclophosphamide combined with tacrolimus and low-dose post-engraftment anti-thymoglobulin as GVHD prophylaxis for patients undergoing peripheral blood stem cell transplantation from haploidentical family donor: A single center analysis - Gao, Wen-hui; Zhu, Jia-yan; Wang, Li-ning; Wan, Ming; Wang, Ling; Devillier, Raynier; Jiang, Jie-ling; Blaise, Didier; Hu, Jiong (Frontiers in Medicine, 2023)
Introduction Post-transplantation cyclophosphamide (PT-Cy) use is a recent graft-versus-host disease (GVHD) prophylaxis strategy for patients undergoing allogeneic stem cell transplantation (allo-HSCT). PT-Cy combined with two immunosuppressants is now widely used after haplo-identical (haplo) and HLA-matched peripheral blood stem cell (PBSC) transplantations with promising GVHD and relapsefree survival (GRFS) probabilities. Although appealing, these results may benefit from improvement notably outside matched sibling donor transplantation, and should be investigated in various ethnic populations. Methods Therefore, we report our experience of GVHD prophylaxis regimen combining PT-Cy and tacrolimus with addition of post-engraftment low-dose anti-thymocyte globulin (ATG) in allogeneic stem cell transplantation from haplo-identical donors (Haplo). Sixtyseven patients were included in the analysis. All patients received myeloablative or intensified sequential conditioning regimen. Results The median follow-up was 521 (range, 10~991) days. The cumulative incidences of 100-day grade II-IV acute GVHD was 14.9±4.4%, and no case of grade III-IV acute GVHD was documented. The cumulative incidences of 2-yearchronic GVHD and moderate-to-severe chronic GVHD were 25.4±5.4% and 11.9±4%, respectively. The non-relapse mortality at day+100 and 2year were 7.5±3.2% and 9.0±3.5%, respectively. The cumulative incidence of relapse at 2year was 16±6.4%. The 2-year probability of DFS and OS were 73.8% (95%CI, 61.5~88.4%) and 72.5% (95% CI, 57.1~92.1%), respectively. The 2-year GRFS was estimated as 63.6% (95%CI, 50.6~80%). Discussion Our results suggested that a combination of PT-Cy, tacrolimus, and low-dose post-engraftment ATG was a promising GVHD prophylaxis with low incidence of acute GVHD in the haplo-transplantation setting.